Five-Year Molecular Surveillance Reveals Widespread Foodborne Enteric Viruses in Bivalve Mollusks From Golfo Nuevo, Argentina - Frydman, Camila Ayelén (2025)
The present investigation conducted a 5-year longitudinal survey (August 2018–March 2023) of enteric viruses in bivalve mollusks (n = 390) collected from Golfo Nuevo, Puerto Madryn, Argentina. Samples were processed following ISO 15216-1:2017 guidelines. Norovirus genogroups I/II (NoV GI/GII), rotavirus A (RVA), hepatitis A (HAV) and E (HEV) viruses, and adenovirus (AdV) were detected and quantified by RT-qPCR/qPCR, genotyped, and subjected to phylogenetic analysis. At least one virus was detected in 40.7% of composite samples. AdV exhibited the highest prevalence (56.6%), while NoV GII and RVA were detected in 12.4% of samples; HEV and HAV were detected in 5.3% and 4.4%, respectively, and NoV GI was not detected. Mean viral loads ranged from 4.8 to 6.3 log10 genomic copies/g of bivalve mollusks. Temporal trends revealed a significant decline in detection post-pandemic for RVA, NoV GII, and HAV, while AdV and HEV rates remained stable. Genotyping identified pandemic variant NoV GII.4[P16], RVA G8P[1], HAV IA, and AdV A31. These results provide the first comprehensive baseline of enteric virus contamination in Patagonian shellfish. Routine virus monitoring and evidence-based control measures are therefore imperative to safeguard public health and to align Argentine bivalve mollusks with international safety standards.